1992
DOI: 10.1113/expphysiol.1992.sp003573
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between secretin and cholecystokinin‐octapeptide in the exocrine rat pancreas in vivo and in vitro

Abstract: SUMMARYThis study investigates the interaction between physiological doses of the synthetic gut hormones, cholecystokinin-octapeptide (CCK8) and secretin on pancreatic juice secretion in the anaesthetized rat and on amylase secretion and Ca2l and Mg2+ mobilization in isolated pancreatic segments and acinar cells. CCK8 (150 pmol kg-1 h-1) and secretin (100 pmol kg-1 h-1) evoked marked time course increases in pancreatic juice flow, total protein output and amylase secretion in the anaesthetized rat when adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
(31 reference statements)
0
20
0
1
Order By: Relevance
“…However, the cellular mechanism(s) of the potentiation of fluid and enzyme secretion is still not clear. It is also possible that two or more intracellular mediators, including cellular Ca¥, cyclic AMP, protein kinase C and tyrosine kinase, are involved since two secretagogues acting via two or more different stimulus-secretion coupling pathways can potentiate one another (Schulz & Stolze, 1980;Jensen & Gardner, 1981;Williams, 1984;Singh, 1985b;Singh et al 1992). …”
Section: Immunohistochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…However, the cellular mechanism(s) of the potentiation of fluid and enzyme secretion is still not clear. It is also possible that two or more intracellular mediators, including cellular Ca¥, cyclic AMP, protein kinase C and tyrosine kinase, are involved since two secretagogues acting via two or more different stimulus-secretion coupling pathways can potentiate one another (Schulz & Stolze, 1980;Jensen & Gardner, 1981;Williams, 1984;Singh, 1985b;Singh et al 1992). …”
Section: Immunohistochemistrymentioning
confidence: 99%
“…For example the phorbol esters can potentiate the secretory actions of ACh and noradrenaline (NA) (Singh, 1985a;Francis & Singh, 1990) and attenuate enzyme secretion evoked by CCK-8 (Ansah et al 1986;Francis et al 1990a). Similarly, secretin can attenuate the secretagogue effect of CCK-8 and activation of intrinsic nerves in the rat pancreas (Singh et al 1992;Wisdom et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…табл.1). Отже, посилення секреції панкреатичного соку може бути пов'язано з ацидифікацією дванадцятипалої кишки, що в свою чергу викликає вивільнення секретину та холецистокініну -стимуляторів зовнішнь-осекреторної функції підшлункової залози [24]. На 68-му добу перебігу патології об'єм базальної панкреатичної секреції зменшився до 0,5 -1,0 мкл/год, тобто у тварин спостері-галася екзокринна недостатність підшлунко-вої залози, що відповідає клінічній картині хронічного панкреатиту.…”
Section: результати та їх обговоренняunclassified
“…In several instances, workers have reported either a potentiation or an attenuation of secretory parameters between secretagogues (Jensen & Gardner, 1981;Singh, 1985;Ansah, Dho & Case, 1986;Willems, Van Nooij, Haenen & De Pont, 1987;Rosh, Schusdziarra, Wolf & Classen, 1989;Salido, Francis, Camello, Singh, Madrid & Pariente, 1990;Singh, Lennard, Salido, Wisdom, Render, Pozo & Pariente, 1992). However, no study has hitherto demonstrated any interaction between the gut hormones and activation of intrinsic secretomotor nerves in the regulation of exocrine pancreatic secretion.…”
Section: Introductionmentioning
confidence: 99%